Sentinel lymph node biopsy for breast cancer using indocyanine green fluorescence visualization - A. D. Zikiryakhodzhaev; E. K. Saribekyan; D. V. Bagdasarova; L. V. Malishava; F. N. Usov; M. V. Starkova (Biomedical Photonics, 2020)
We presented the preliminary results of sentinel lymph node biopsy (SLN) using the method of fluorescent visualization with the indocyanine green. The study included 40 breast cancer patients with the prevalence of the cTis-2N0M0 process. 1 ml of Indocyanine Green (ICG) aqueous solution was administered periareolarly and subcutaneously from the tumor side with total drug dose of 5 mg. In the following few minutes the ICG trail along the lymphatic vessels was observed by its fluorescence in the infrared spectral range using a special camera with image transmitted to a computer screen. After the trail reached the axillary region and broke off, skin and subcutaneous tissue incision in axillary area was made, and the superficial fascia was dissected. The first contrasted lymph nodes were extracted. The incidence of SLN was 92.5%. Metastases were detected in 20% of cases. On average, it took 17.6 minutes to identify and remove the SLN. In 7 patients the use of the fluorescent SLN detection method was combined with radioisotope (Technefite 99m Tc colloid) – in all cases the same SLN was identified. The use of the ICG lymphotropic dye with the subsequent detection of SLN by the fluorescence method makes it possible to diagnose the status of SLN with a high degree of accuracy and can be comparable in effectiveness with the isotopic method. The specificities of lymphatic drainage were found out with the use of fluorescence lymphography: inverse dependence of the lymphatic drainage rate on the body mass index and breast size, and absence of dependence on degree of ptosis of breast.